Risk factors for suicidal ideation in university students - Aguilar Chávez, Pablo Valentino; Talavera Cubas, Marco Antonio; Flores Lezama, Marilú Trinidad; Rojas Huatay, Nicol Yajaira (Revista Cuidarte, 2026)
Highlights • Suicidal ideation occurs in 25% of university students and is associated with a 5.4-fold increased risk of suicide attempt. • Sexual violence is associated with a 3.4-fold higher risk of suicidal ideation, a critical factor previously underestimated in this population. • Traumatic experiences during childhood or adolescence are associated with a 2.4-fold increased likelihood of developing suicidal thoughts among university students. • Early identification of factors such as sexual orientation, substance use, and clinical diagnoses is crucial for suicide prevention in academic settings. Introduction: Suicide is the second leading cause of death among university students, with one in four reporting having contemplated taking their own life. This issue is closely associated with deterioration in mental health status and exposure to prior traumatic experiences. Objective: To determine the risk factors associated with suicidal ideation among university students in the La Libertad region, Peru. Materials and Methods: A quantitative, non-experimental study with a multivariable analytical design. The study involved 380 university students selected through simple random probability sampling. The Beck Scale for Suicidal Ideation, adapted to the Peruvian context (Cronbach’s alpha = 0.800), and a questionnaire on sociodemographic and psychological factors were administered online. The analysis included logistic regression and estimation of odds ratios to determine risk probabilities. Results: Suicidal ideation was reported by 25% of participants and was more prevalent among students aged 17–21 years, females, those from socioeconomic level C, and first-year students. The factors most strongly associated were depression (OR=5.437; 95% CI [3.136-6.866]), sexual violence (OR=3.437; 95% CI [2.328-5.074]), and traumatic experiences during childhood/adolescence (OR=2.402; 95% CI [1.662-3.472]). The models explained between 36.9% and 76.5% of the variance in suicidal ideation. Discussion: The magnitude of the association between depression and suicidal ideation exceeds previous estimates, suggesting context-specific cultural factors in Peru. Sexual violence emerges as a critical, previously underestimated factor. Conclusions: Sociodemographic factors such as substance use, family loss, and sexual orientation, together with psychological aspects such as depression, violence, and trauma, are significant predictors of suicidal ideation, with the latter showing the highest risk likelihood. How to cite this article: Aguilar Chávez Pablo Valentino, Talavera Cubas Marco Antonio, Flores Lezama Marilú Trinidad, Rojas Huatay Yajaira Nicol. Risk factors for suicidal ideation among university students. Revista Cuidarte. 2026;17(1):e5034. https://doi.org/10.15649/cuidarte.5034